2020
DOI: 10.1093/glycob/cwaa034
|View full text |Cite
|
Sign up to set email alerts
|

Glycan characterization of pregnancy-specific glycoprotein 1 and its identification as a novel Galectin-1 ligand

Abstract: Pregnancy-specific beta 1 glycoprotein (PSG1) is secreted from trophoblast cells of the human placenta in increasing concentrations as pregnancy progresses, becoming one of the most abundant proteins in maternal serum in the third trimester. PSG1 has seven potential N-linked glycosylation sites across its four domains. We carried out glycomic and glycoproteomic studies to characterize the glycan composition of PSG1 purified from serum of pregnant women and identified the presence of complex N-glycans containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 88 publications
1
19
0
Order By: Relevance
“…PSGs contain multiple potential N-glycosylation sequences and also potential sites for O-glycosylation and evidence of glycosylation have been indicated by lectin binding studies [151]. Recently, we have characterized PSG1 n detail in terms of its glycosylation [152]. We showed that PSG1 contains multi-antennary complex N-glycans with high levels of α2-3 sialic acid capping.…”
Section: Glycosylation In Pregnancy Term and Preterm Labormentioning
confidence: 83%
“…PSGs contain multiple potential N-glycosylation sequences and also potential sites for O-glycosylation and evidence of glycosylation have been indicated by lectin binding studies [151]. Recently, we have characterized PSG1 n detail in terms of its glycosylation [152]. We showed that PSG1 contains multi-antennary complex N-glycans with high levels of α2-3 sialic acid capping.…”
Section: Glycosylation In Pregnancy Term and Preterm Labormentioning
confidence: 83%
“…These appear to attract, activate, and induce apoptosis of maternal immune cells that might otherwise attack invading trophoblast ( 134 ). Intriguingly, PSG-1 is a ligand for galectin-1 ( 135 ).…”
Section: Immunosuppressionmentioning
confidence: 99%
“…The high expression level of PSG1 during the third trimester permitted the isolation of native PSG1 from pooled serum of pregnant women using affinity chromatography allowing for a comprehensive glycomic and glycoproteomic investigation of the native protein ( 234 ). PSG1 has seven potential N-linked glycosylation sites across its four Ig-like domains designates as N, A1, A2 and B2 but only four sites mapping to the N, A1 and A2 domains of the protein were confirmed to be occupied by glycans ( 234 ). The presence of multiantennary and poly-N-acetyl-lactosamine (LacNac) elongated moieties with mainly alpha2,3-linked sialic acid terminals, suggested that PSG1 could interact with members of the galectin family.…”
Section: Galectins and Pregnancy-specific Glycoproteinsmentioning
confidence: 99%
“…Gal-1 binds to native and recombinant PSG1 in a carbohydrate-dependent manner, demonstrated by the inhibition of PSG1-gal-1 binding by lactose and failure of PSG1 generated in insect cells or N-acetylglucosaminlytransferase I (GnTI)-deficient cells, which carry only mannose-type glycans, to interact with gal-1. In addition, removal of N-linked oligosaccharides from the N- and A2- PSG1 domains by treatment with the amidase PNGase F prevented their binding to gal-1 ( 234 ). Changes in glycosylation could add further complexity to the regulation of important biological processes in pregnancy known to be regulated by both extracellular galectins and their ligands, including the PSGs.…”
Section: Galectins and Pregnancy-specific Glycoproteinsmentioning
confidence: 99%